Pengembangan Modul Pembelajaran Biologi Materi Sistem Reproduksi Terintegrasi Al-Quran Bermuatan Keterampilan Abad-21 Di SMA Swasta Citra Medang Deras - Chodijah Anurja; Ira Suryani; Khairuna (GLOBAL SCIENTS PUBLISHER, 2025)
This research is development research (RnD) which aims to produce an Al-Quran integrated reproductive system learning module biology contains 21st century skills that is valid, practical, and effectively used in learning. This module development research refers to the 4-D development model which has 4 stages namely define, design, development, and dissemination which have been revised and tested on a limited scale in the field. The research instrument used was a validation sheet, student response questionnaires, and a test of learning outcomes in the form of 20 numbered multiple choice questions. The data analysis techniques used are validity data analysis, practically data analysis, and effectiveness data analysis. The result showed that the Al-Quran integrated reproductive system learning module biology contains 21st century skills as a whole had good quality in teaching and learning activities. The level of validity of the module can be seen from the result of the percentage of validators of material experts by 83% with very valid criteria, from media experts by 81,6% with very valid criteria, and from Al-Quran experts by 84,6% with very valid criteria. The practicality level of the module is seen from the student responses obtained from the overall percentage of the small group test of 79,8% with interesting criteria and the large group test of 84,4% with very interesting criteria. Then the level of effectiveness of the module seen from the learning outcomes of student obtained the average value of the level of mastery of students that is equal to 85,5% in the very effective category with the percentage of student learning completeness of 100%. Thus, it can be concluded that the module developed with the 4-D model is valid, practical, and effective so that it is feasible to be used as teaching material for students of class XI MA/SMA, especially on reproductive system material.